THE INFLUENCE OF PRICE, USER EASE AND TRUST ON CONSUMER BUYING INTEREST ON THE E-COMMERCE PLATFORM ON THE LAZADA SITE IN LHOKSEUMAWE CITY - Mahfuza; T. Edyansyah; Muchsin; Khairina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to analyze the influence of price, user convenience, and trust on consumer interest in using the Lazada E-commerce platform in Lhokseumawe City. In the increasingly developing digital era, E-commerce has become one of the primary choices for consumers to purchase goods and services. Factors such as competitive prices, ease of use, and consumer trust level are substantial aspects that influence consumer interest. The research method used is a survey with a quantitative approach, and collected through questionnaires distributed to Lazada consumers in Lhokseumawe City. The research sample was taken using a purposive sampling technique, with 100 respondents, and the data analysis uses multiple linear regression to see the influence of each independent variable on the dependent variable. The research results show that the three variables, namely price, user-friendliness, and trust, positively and significantly influence consumer interest in using the Lazada platform. Of these three variables, consumer trust in the platform has the most dominant influence compared to other variables. It shows that, in the context of E-commerce, consumer trust is a key factor that platform providers should pay attention to increase consumer interest. It concludes that to increase consumer interest in Lhokseumawe City, Lazada should continue to maintain competitive prices, improve easy and comfortable user experience, and build and maintain consumer trust through various effective strategies. This research can contribute to developing marketing strategies and improving service quality on the Lazada E-commerce platform.